Counselling psychology's genotypic and phenotypic features across national boundaries. Issue 2 (2nd April 2016) - Hutman, Heidi; Lichtenberg, James W.; Goodyear, Rodney K.; Overland, Emily A.; Tracey, Terence J. G.
Abstract : This article integrates the survey results presented in the introductory article of this journal issue as well as the articles describing counselling psychology in each of the countries covered in the issue to examine the international character of counselling psychology. Specifically, it addresses the similarities and differences in the histories, education and training, demographics, and practice characteristics of the specialty within and across these national boundaries. The article concludes with an analysis of the value dimensions describing the international character of counselling psychology and addresses where the different countries place themselves along the two dimensions that were identified: Dimension 1 capturing basic research as different from most of the other values, and Dimension 2 being defined by an applied client focus versus a more indirect clinical perspective (i.e. social justice and research adding to the knowledge base).